Pengaruh Sharia Compliance dan Good Corporate Governance Terhadap Profitabilitas Bank Umum Syariah Indonesia Periode 2017-2024 - Livia Rizca Firlizda; Moh Mukhsin; Ahmad Fatoni (Universitas Muhammadiyah Surabaya, 2025)
This study aims to examine the effect of Sharia Compliance, proxied by the Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Non-Halal Income, as well as Good Corporate Governance, proxied by the number of Board of Directors and Sharia Supervisory Board members, on profitability (Return On Assets or ROA) in Islamic Commercial Banks (ICBs) in Indonesia. This research utilizes secondary data in the form of annual financial reports from ICBs registered with the Financial Services Authority (OJK) for the 2017–2024 period and is analyzed using panel data methods with the assistance of EViews 12. The results show that the Profit Sharing Ratio has a significant positive effect on Return On Assets. However, the Zakat Performance Ratio and Non-Halal Income have no significant effect on ROA. On the other hand, the number of Sharia Supervisory Board significantly influences bank profitability. These findings highlight the importance of optimizing profit-sharing schemes and strengthening Sharia governance to enhance the financial performance of Islamic Commercial Banks in Indonesia.